Praktik Akad Gadai dengan Jaminan Lahan /Sawah dan Gadai Emas di Kecamatan Mempura Kabupaten Siak Berdasarkan Hukum Islam - Muhammad Azani (Perspektif Hukum, 2015)
Lien contract undertaken by the community in the District Mempura Siak is pledge of land/fields. However, whether the lien contract is in reality a pledge as described in Islamic law. The researched issues are focused on the level of understanding of the community in the District Mempura Siak about the sharia lien contract; the practice of pledge land/fields that has been done by the community in the District Mempura Siak; and the practice of buying gold then pawned again when the gold price higher. Results of research show that 1) the level of understanding of the community in the District Mempura Siak about sharia pawning is very well with indications that most of the community involved in the activity of sharia pawn can understand as an alternative financing based on Islamic law; 2) lien contract practice that has been done by the community in the District Mempura Siak is not the Sharia lien contract based Islamic law. Practice is more accurately described as muzara'ah, which is a form of cooperation between landowners and land managers with profits shared according to the agreement. 3) The practice of buying gold then pawned again at the time of high gold prices does not constitute as a lien contract practice based on Islamic law, but more as buying and selling gold. This practice has been in the category of speculation on the price of gold, as gold prices are subject to change-change according to market gold in the international market.